O pożytkach interpretacyjnych brytyjskiej ﬁlozoﬁ i analitycznej - Barankiewicz, Tomasz (Wydawnictwo Naukowe UAM, 2015)
The article enumerates the main models of language analysis which constitute the achievements of British analytic philosophy of the 20th century. They are as follows: 1. descriptive analysis of linguistic expressions, characteristic of the philosophy of G.E. Moore; 2. analysis as logical reconstruction, so called a “hard” analytical approach, proposed by G. Frege and B. Russell as well as L. Wittgenstein from the early period of his views; 3. therapeutic interpretation of language, when it is assumed that philosophical problems stem from errors and faulty language (J.L. Austin, G. Ryle and L. Wittgenstein of the second period of views); 4. the model of connective analysis, which is based on the assumption that concepts form a well-ordered system, where each of the elements can be properly interpreted only through mutual relations, i.e. through a deﬁ ned position and function with respect to the other elements of the system (P.F. Strawson).Common among Polish theoreticians of law, mainly by M. Zieliński, the principle omnia sunt interpretanda (all and always should be interpreted) points out to the conditions of wider understanding of the choice of legal interpretation methods. The presented models of analysis of the British twentieth century analytic philosophy justify the necessity of the use of interpretation because of the full “restoration” of the contents of a legal norm. Too narrow approaches to interpretative analysis of lan-guage, conﬁ ned merely to so-called “therapeutic” treatments, removing ambiguity, lack of clarity or focus, as well as error in the legal text, should be regarded as untenable. After reviewing the main models of analysis, it can be reasonably argued that in the phenomenon of language, its interpretation and openness to interpretation, as well as liaison with the pragmatic elements resulting from social communication,
About the interpretative beneﬁ ts of British analytical philosophy
Keywords: interpretation of the law; clariﬁcation; methods of linguistic analysis